Histopathology of Gills and Liver of Tilapia (Oreochromis niloticus) Infected with Streptococcus agalactiae and Fed with Fermented Herbal Medicine - Siallagan, Romensius Anggi AW; Syawal, Henni; Riauwaty, Morina (Jurnal Perikanan dan Kelautan, 2025)
Streptococcus agalactiae is a pathogen that causes significant losses in tilapia (Oreochromis niloticus) aquaculture. One alternative control is the use of natural ingredients such as fermented herbs. This study aims to analyze changes in the histopathological structure of the gills and liver of tilapia fish fed with feed containing fermented herbs after being infected with S. agalactiae. The research was conducted from March to December 2023 at the Laboratory of Parasites and Fish Diseases, Faculty of Fisheries and Marine Sciences, Universitas Riau and Bukittinggi Veterinary Center. The method used was a one-factor, completely randomized design (CRD) with five treatments and three replicates. The treatments consisted of negative control (Kn), positive control (Kp), and three feed treatments with fermented herbal medicine doses of 100 (P1), 125 (P2), and 150 mL/kg feed (P3). S. agalactiae infection was carried out on day 31 at a dose of 10⁸ CFU/mL. The results showed that the P3 treatment gave the best results, characterized by minimal damage to gill tissue (only hypertrophy) and liver (mild vacuolar degeneration) and the highest survival rate of 83.33%. In conclusion, adding fermented herbal medicine at a dose of 150 mL/kg feed can increase the immunity of tilapia against S. agalactiae infection, as shown through the improvement of organ tissue structure and improved survival